The Influence of Human Resource Professionalism, Village Asset Management, Asset Utilization Optimization, and the Role of BUMDes Human Resources on Increasing Village-Generated Revenue (PADes) - Tri Sumiyanti; Taswan; Anisa Kusumawardani; Muhammad Farras Alfitra; Jati Widya Iswara; Abdul Fajar (Journal of Creative Power and Ambition (JCPA), 2026)
The Influence of Human Resource Professionalism, Village Asset Management, Asset Utilization Optimization, and the Role of BUMDes Human Resources on Increasing Village-Generated Revenue (PADes)